Experiencias de consumo como nuevos productos turísticos. La promoción de festivales y eventos en la Ciudad Autónoma de Buenos Aires - Rodríguez, Luciana Mabel (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2019)
Given the proposition of competing in the international tourism market, cities are promoted by their local governments, offering a series of attractions increasingly oriented towards active forms of consumption, with emphasis on intangible cultural resources, what is defined as creative tourism. In this context, urban marketing is presented as the dominant instrument of tourism policy, a means to launch these new products to their consumers. The city of Buenos Aires does not escape this dynamic. Immersed in an intense tourist promotion undertaken by its local government, it incorporates to the traditional tourist offer new attractions based on cultural practices, as part of the development of competitive urban experiences. Through a qualitative methodology, based on the systematization and analysis of the Festivals and Events offered through its official tourism page, the article analyzes how creative tourism is capitalized for the creation of new tourism products in the city of Buenos Aires. Aires the results obtained confirm a growing trend in creative tourism linked to the development of gastronomic and artistic products, with a reduction of state intervention and the primacy of marketing in its development.